Oxidative stress and altered levels of oxidants and antioxidants in acute ischemic stroke patients in a region of east turkey - Özbey, Ülkü; Seyran, Ayşe; Erişir, Mine; Özel, Seda (My University, 2012)
Background and purpose: Ischemic stroke is one of the most important diseases causing severe disability and death. Hypertension is the most important risk factor in strokes, representing roughly 70% of all cases. Oxidative stress plays an important role in acute ischemic stroke (AIS) pathogenesis. It is believed to be one of the mechanisms taking part in neuronal damage in stroke. Free radical formation and subsequent oxidative damage may be a factor in stroke severity. In 28 patients with AIS and 28 healthy individuals were investigated with regard to relationship between ischemic-stroke and glutathione peroxidase (GSHPx), catalase (CAT) activities, malondialdehyde (MDA), glutathione, ?-carotene, vitamin A levels. Methods: GSH-Px, CAT activities and MDA, GSH, vitamin A, ?-carotene levels were measured by spectrophotometry in 28 subject (15 females and 13 males aged 67.1±13.3years) with AIS and 28 age-matched healthy subjects (13 females and 15 males aged 65.9 ± 10.1). Results: In the patients with acute ischemic stroke, GSH-Px activity and MDA, GSH, vitamin A levels were found increased (p<0.001). Whereas there was no significant difference in level of ?-carotene and CAT activity between AIS patients and control group (p>0.005). Conclusions: Our results suggest deleterious effects of oxidative stress on clinical outcome in AIS. There was a significant increase in levels of MDA, GSH-Px and GSH. GSH elevation seemed to be a part of adaptive mechanisms.
Keywords: Antioxidants; Oxidants; Oxidative stress; Risk factors; Stroke ischemic